MODIFIKASI CAMPURAN BETON ASPAL HRS-WC DENGAN MENGGUNAKAN BAHAN ANTI STRIPPING - Rikki Sofyan Rizal; Anni Susilowati; Eko Wiyono (Universitas Widyatama, 2022)
In road development, the main challenge is the pavement, especially asphalt concrete which breaks down quickly. The type of damage that is commonly found in Indonesia is premature surface damage, the visible symptoms of which are surface peeling, surface rutting, grain release and cracks. This typical damage for asphalt concrete pavement layers, is usually caused by low asphalt adhesion, this is marked by the release of grains due to no longer cohesion by asphalt which eventually gives water the opportunity to penetrate and destroy the asphalt concrete matrix. As a result, the mixture becomes loose and there is a lot of asphalt peeling on the surface layer. Based on this background, it is necessary to study the modification of the gap graded asphalt concrete mixture for Lataston HRS-WC by using anti-stripping materials. The purpose of conducting this research is to obtain the effect of anti-stripping materials in the gap graded asphalt concrete mixture on the properties of the Marshall test results in accordance with the 2018 Highways specifications. From the results of the tests carried out, the Optimum Asphalt Content (KAO) is 7.4%. With the KAO value, a test sample was made with the addition of Wetfix Be with a concentration of 0.2; 0.3 ; 0.4 and 0.5. The results obtained with the addition of Wetfix Be 0.30% increased the stability value to 1423.12 kg and Mashall quotient to 400.88 kg/mm. A high Marshall Quotent value indicates the mixture is stiff and has low flexibility.